2018
DOI: 10.1038/s41598-018-33618-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term enhancement of cognitive functions and music: A three-channel model

Abstract: Short-term effects of music stimulus on enhancement of cognitive functions in human brain are documented, however the underlying neural mechanisms in these cognitive effects are not well investigated. In this study, we have attempted to decipher the mechanisms involved in alterations of neural networks that lead to enhanced cognitive effects post-exposure to music. We have investigated the changes in Electroencephalography (EEG) power and functional connectivity of alpha band in resting state of the brain afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
(84 reference statements)
0
18
0
1
Order By: Relevance
“…For example, it has been proposed that complex neurocognitive processes may also arise from the brain's global modular structure, that is, to the degree of integration and segregation among brain subsystems (Ito et al, 2019). This view is supported by recent studies that linked the brain's intrinsic organization to the predisposition of individual behavioral patterns (Godwin et al, 2015;Hilger et al, 2017;Gupta et al, 2018).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, it has been proposed that complex neurocognitive processes may also arise from the brain's global modular structure, that is, to the degree of integration and segregation among brain subsystems (Ito et al, 2019). This view is supported by recent studies that linked the brain's intrinsic organization to the predisposition of individual behavioral patterns (Godwin et al, 2015;Hilger et al, 2017;Gupta et al, 2018).…”
Section: Introductionmentioning
confidence: 66%
“…Global modularity parameters obtained during a task-free state may be interpreted as describing intrinsic organizational principles that quantify how efficiently a brain is represented by subnetworks, or modules (Gallen and D'Esposito, 2019). Previous studies have reported various associations between whole-brain parameters and behavior, such as between the modular organization and intelligence (Hilger et al, 2017), between inter-modular connections and awareness (Godwin et al, 2015), and between global efficiency and short-term memory skills (Gupta et al, 2018). Expanding on these studies, our findings suggest that brain-behavior associations may exist at multiple hierarchical levels of brain architecture, especially regarding module topography-dependent measures.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of other unconventional (Unconventional means of enhancement are methods involving deliberately created nootropic drugs, neural implants, brain–computer interface and other new senses.) and more contemporary means of vigilance enhancers have also been reported, such as pharmaceuticals [25]; video games [26,27]; transcranial alternating current stimulation (tACS) and transcranial direct current stimulation (tDCS) [28,29,30,31,32,33]; tactile and rhythmic haptics [34,35,36,37]; integrating new challenges into the primary task [38]; music [39,40]; and binaural auditory beats [41,42]. Resulting studies have reported contradictory findings regarding the efficacy of the aforementioned enhancement techniques, which have hampered the progress of further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that spectral powers in typical frequency bands are closely related to vigilance decrement. Data analysis presented in this study involved five frequency bands, [delta (< 4 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and wide/full (0.1-30 Hz) frequency bands].The main findings of research using EEG vigilance level assessment suggest that low-frequency brain rhythms (4-12 Hz) increase during vigilance decrement. An increase in low-frequency rhythms is an indication of decreased alertness, corroborating with behavioral impairment of vigilance decrement [33].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have utilized a wide range of traditional and computerized enhancement methods to improve sustained attention. These methods include: mental training [7], meditation [8], sports [2], caffeine [2], nicotine [9], herbal extraction [10], chewing gum (CG) [11], fragrances exposure [12], playing video games (VG) [13], applying transcranial alternating current stimulation (tACS) [14], or transcranial direct current stimulation (tDCS) [15], tactile and rhythmic haptics (RHP) [16], integrating of multiple tasks (IMT) [17], music [18] and binaural beat (BB) stimulation [19]. We have recently conducted a comprehensive review on the aforementioned enhancement methods on vigilance levels in the context of work, monitoring/surveillance, driving, learning, performing cognitive and memory tasks, typing, and sports [1].…”
Section: Introductionmentioning
confidence: 99%